2008
DOI: 10.1097/ta.0b013e31816543dd
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Endogenous Estrogens are Associated With Death in the Critically Injured Adult

Abstract: Background: Sex hormones exhibit predictable changes in their physiologic patterns during critical illness. Endogenous estrogens are elevated in both genders as a result of the peripheral conversion of androgens to estrogens by the aromatase enzyme. Elevated endogenous estrogens have been associated with death in medical and mixed surgical intensive care unit (ICU) patients. Our objective was to determine the relationship between endogenous estrogens and outcomes in critically injured patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 36 publications
4
58
0
3
Order By: Relevance
“…Others have noted that the presence of sex hormones (estrogens) in premenopausal people, lead to harm and worse outcomes in the setting of acute sepsis or pneumonia. 5,6,34 This appears an area for future investigation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Others have noted that the presence of sex hormones (estrogens) in premenopausal people, lead to harm and worse outcomes in the setting of acute sepsis or pneumonia. 5,6,34 This appears an area for future investigation.…”
Section: Discussionmentioning
confidence: 93%
“…2,3 Sex hormones and sex-related gene polymorphisms could potentially enhance or suppress the immune system and affect outcomes in women. [4][5][6][7][8][9][10] Epidemiologic studies have produced conflicting results, 4,[11][12][13][14][15][16][17] , with some suggesting that in addition to gender, menopausal status may influence patient outcome. 4,13,[18][19][20] Clinical studies have suggested that male gender is associated with a greater incidence of nosocomial pneumonia in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 In our study characterizing serum hormones acutely after TBI, elevated estradiol in particular was associated with mortality and poor outcomes 6 months postinjury. 10 These findings suggest that tissuespecific aromatase activity significantly influences the hormone profiles, and there are different mechanisms of hormone physiology at play in the CSF versus serum compartments.…”
Section: Garringer Et Almentioning
confidence: 99%
“…We showed high E 2 levels in female patients and a correlation between E 2 and disease severity. E 2 level increases in critically ill patients [22,23] and is reported to be associated with mortality [24]. Elevated aromatisation of adrenal androgens to E 2 mediated by cytokines is proven to result in increased serum E 2 levels [23,25].…”
Section: Discussionmentioning
confidence: 99%